Use of Hypermedia Tools for End-User Development - Ortiz Chamorro, Sebastián S. (2010)
Software development tools aimed at end-users tend to employ various forms of visual programming because these users find textual programming very difficult to learn. However, visual programming has known scalability issues. As an alternative, we propose hypertextual programming; a technique that represents the program as hypertext and allows the user to both browse it and manipulate it mainly by using navigation. This technique leverages the users' ability to navigate in hyperspace, a widely available skill, to edit the program under development. In order to reap the benefits of this technique, adequate hypertextual editors must be built. Many of the lessons learned in the web engineering area can be used to deal with this problem. This paper discusses the state of the current research efforts behind this novel programming technique.